DAMPAK POPULASI DAN MOBILITAS PERKOTAAN TERHADAP PENYEBARAN PANDEMI COVID-19 DI JAKARTA - Rizki Adriadi Ghiffari (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2020)
The Covid-19 disease outbreak has spread to more than 200 countries, including Indonesia. Epicenter of the spread of the disease is in big cities that have been designated as local transmission, including the city of Jakarta. In addition to the ability of virus transmission, the spread of infectious diseases directly is also influenced by the characteristics of the population and human mobility as a breeding ground for viruses. Based on the results of the correlation test, it was found that mobility within the city and external mobility, had an intermediate effect on the spread of COVID-19 disease. While the human development index, population growth, poor population, and vulnerable age variables also have a low impact on the spread of this disease. The ability to detect and respond to large-scale disease outbreaks is needed, and effective population mobility restrictions are needed to control the spread of this disease.Key words: Urban Demographic, Urban Mobility, Covid-19 Pandemic Wabah penyakit Covid-19 telah menyebar ke lebih dari 200 negara, termasuk Indonesia. Episentrum penyebaran penyakit berada di kota-kota besar yang telah ditetapkan sebagai transmisi lokal, diantaranya Kota Jakarta. Selain kemampuan penularan virus, penyebaran penyakit menular langsung juga dipengaruhi oleh karakteristik populasi dan mobilitas manusia sebagai inang perkembangbiakan virus. Berdasarkan hasil uji korelasi didapatkan bahwa mobilitas di dalam kota dan mobilitas dari luar kota, berpengaruh dalam tingkat menengah terhadap penyebaran penyakit COVID-19. Sedangkan variabel indeks pembangunan manusia, pertumbuhan penduduk, penduduk usia rentan, penduduk miskin juga berpengaruh secara rendah terhadap penyebaran penyakit ini. Diperlukan kemampuan mendeteksi dan merespon wabah penyakit skala besar, serta pembatasan mobilitas penduduk yang efektif untuk dapat mengendalikan penyebaran penyakit ini.Kata Kunci: Karakteristik Demografi, Mobilitas Penduduk, Pandemi Covid-19